2008
DOI: 10.1158/1078-0432.ccr-07-1652
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Clinical and Pharmacokinetic Study of Plitidepsin as a 1-Hour Weekly Intravenous Infusion in Patients with Advanced Solid Tumors

Abstract: Purpose: Plitidepsin, given as a 1-hour weekly i.v. infusion for 3 consecutive weeks during a 4-week treatment cycle, was investigated in patients with solid tumors to determine the maximum tolerated dose and the recommended dose (RD) using this administration schedule. Experimental Design: Consecutive cohorts of patients with metastatic solid tumors or non^Hodgkin's lymphomas were to be treated at escalating doses of plitidepsin in a conventional phase I study including pharmacokinetic analyses of plitidepsin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
(27 reference statements)
7
25
0
Order By: Relevance
“…Plitidepsin induces an early oxidative stress response, which results in a rapid and sustained activation of the EGF-R, the non-receptor protein tyrosine kinase Src, the serine threonine kinases c-Jun NH2-terminal kinase, and p38 mitogen-activated protein kinase. These early events rapidly trigger the induction of the mitochondrial apoptotic pathway via cytochrome c release, activation of the caspase cascade, and activation of protein kinase C, which seems to exert an important effector role in mediating cellular death induced by the drug [146]. In a phase I clinical trial, the single MTC patient showed disease stabilization [146].…”
Section: Novel Treatment Modalities: Preclinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plitidepsin induces an early oxidative stress response, which results in a rapid and sustained activation of the EGF-R, the non-receptor protein tyrosine kinase Src, the serine threonine kinases c-Jun NH2-terminal kinase, and p38 mitogen-activated protein kinase. These early events rapidly trigger the induction of the mitochondrial apoptotic pathway via cytochrome c release, activation of the caspase cascade, and activation of protein kinase C, which seems to exert an important effector role in mediating cellular death induced by the drug [146]. In a phase I clinical trial, the single MTC patient showed disease stabilization [146].…”
Section: Novel Treatment Modalities: Preclinical Studiesmentioning
confidence: 99%
“…These early events rapidly trigger the induction of the mitochondrial apoptotic pathway via cytochrome c release, activation of the caspase cascade, and activation of protein kinase C, which seems to exert an important effector role in mediating cellular death induced by the drug [146]. In a phase I clinical trial, the single MTC patient showed disease stabilization [146]. Further studies with large patient groups are needed to evaluate the drug’s effect on MTC.…”
Section: Novel Treatment Modalities: Preclinical Studiesmentioning
confidence: 99%
“…The overall safety profile was in accordance with that reported in a previous phase I clinical trial with this single-agent schedule in patients with solid tumors. 12 Of note, many of the side effects commonly induced by cytotoxic agents, such as alopecia, mucositis/stomatitis or clinically relevant myelosuppression, were not characteristic of plitidepsin.…”
Section: Discussionmentioning
confidence: 99%
“…12 The time course of plitidepsin whole blood concentrations in NHL patients was appropriately described by an open,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation